Testing the Correlation Model of Psychological Well-Being, Self-Compassion, and Mindfulness in Married Nurses with the Mediating Role of Alexithymia - Karami , Tayebe; Behboodi, Masoumeh; Janangir , Pantea (KMAN Counseling & Psychology Nexus, 2024)
Throughout married life, various factors affect communication, mental health, and quality of life. Understanding these factors is foundational to strengthening family life. This study aimed to test the correlation model of psychological well-being, self-compassion, and mindfulness in married nurses with the mediating role of alexithymia. The present research employed a descriptive-correlational method. The statistical population included all married nurses in Ilam County during the first half of 2023. The sample comprised 240 nurses selected through convenience sampling. Data collection tools included a demographic questionnaire, the Psychological Well-Being Scale, the Self-Compassion Scale, the Freiburg Mindfulness Inventory, and the Toronto Alexithymia Scale. Data analysis was performed using Amos software version 24. Structural equation modeling (SEM) was applied to evaluate the proposed model, and the bootstrapping method was used to test indirect relationships. The findings revealed that self-compassion and mindfulness could enhance psychological well-being in nurses by reducing alexithymia. It is recommended that the Ministry of Health and Medical Education organizes effective and constructive workshops and seminars focusing on realistic expectations in marital relationships, perceptions and motivations, mindful approaches, and strategies to enhance self-compassion to improve the psychological well-being of nurses